A review of non-destructive techniques applied for measuring quality of oil palm fresh fruit bunches - Chen, Yee Being; Norhashila, Hashim; Bernard, Maringgal; Mohd Hafizz, Wondi (SixScientia Resources, 2020)
The quality of oil palm fruits is evaluated through several characteristics such as the ripeness level, oil content, and free fatty acid. Besides human visual assessment and destructive techniques, another alternative method that provides quality assessment on oil palm fresh fruits bunches (FFB) is through the application of non-destructive techniques. A few of the non-destructive techniques are covered in this review such as machine vision system, visible or near infrared spectroscopy, image processing using relative entropy, fluorescence technique, Kinect camera, and optical sensor system. The main quality parameter that is being evaluated is the ripeness level of the FFB because the maturity of FFB has a direct impact on the quality of the extracted oil that will eventually affect the economic value of palm oil.